Post-National Foundation of Judith Butler’s and Rossi Braidotti’s Relational Subjectivity - Carmichael, Adam Burke (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
This article draws on examples of Indigenous conceptualizations of nationhood to question the post-national foundation of Judith Butler’s and Rossi Braidotti’s theories of affective subjectivity. The article concludes that the responsibility to respect certain political boundaries is necessary in fostering non-oppressive affective relations.